Communication Between Baristas and Coffee By Meraki Consumers - Calista Zahra, Shalma; Nyoman Intan, Desak; Nurfalah, Farida; Dian Lestari, Aghnia (Asian Journal of Social and Humanities, 2024)
The rapid development of modern cities has changed the landscape of the coffee business significantly. The large number of entrepreneurs in this sector creates a variety of food and beverage variants, encouraging the continued development of innovation and creativity. This study aims to find out how the characteristics of communication between baristas and their obstacles are. This study uses a qualitative method by collecting data from interviews with three informants with data triangulation techniques, then observation and study of book and journal literature. The data analysis is with the stages of data display, data reduction, and conclusion. This study discusses the results of interpersonal communication between baristas and consumers at Coffee by Meraki, using characteristics such as the first openness: baristas as communicators can communicate effectively then the service process depends on the responsiveness of the barista to consumer requests, the second is a sense of empathy: baristas will conduct marketing sessions that bring each other closer and create a sense of mutual trust, so there is a mutual bond,  Third, support: Baristas interact directly to greet customers and build communication. Fourth, positivity: baristas must have a positive attitude to create consumer satisfaction and comfort. Fifth: equality: by treating all consumers equally and there is no difference in appearance or social class.